Can Old Animals Reveal New Targets? The Aging and Degenerating Brain as a New Precision Medicine Opportunity for Epilepsy - del Pozo, Aaron; Lehmann, Leanne; Knox, Kevin M.; Barker-Haliski, Melissa (Frontiers in Neurology, 2022)
Older people represent the fastest growing group with epilepsy diagnosis. For example, cerebrovascular disease may underlie roughly 30–50% of epilepsy in older adults and seizures are also an underrecognized comorbidity of Alzheimer's disease (AD). As a result, up to 10% of nursing home residents may take antiseizure medicines (ASMs). Despite the greater incidence of epilepsy in older individuals and increased risk of comorbid seizures in people with AD, aged animals with seizures are strikingly underrepresented in epilepsy drug discovery practice. Increased integration of aged animals into preclinical epilepsy drug discovery could better inform the potential tolerability and pharmacokinetic interactions in aged individuals as the global population becomes increasingly older. Quite simply, the ASMs on the market today were brought forth based on efficacy in young adult, neurologically intact rodents; preclinical information concerning the efficacy and safety of promising ASMs is not routinely evaluated in aged animals. Integrating aged animals more often into basic epilepsy research may also uncover novel treatments for hyperexcitability. For example, cannabidiol and fenfluramine demonstrated clear efficacy in syndrome-specific pediatric models that led to a paradigm shift in the perceived value of pediatric models for ASM discovery practice; aged rodents with seizures or rodents with aging-related neuropathology represent an untapped resource that could similarly change epilepsy drug discovery. This review, therefore, summarizes how aged rodent models have thus far been used for epilepsy research, what studies have been conducted to assess ASM efficacy in aged rodent seizure and epilepsy models, and lastly to identify remaining gaps to engage aging-related neurological disease models for ASM discovery, which may simultaneously reveal novel mechanisms associated with epilepsy.